Innovation in Work Practices: A Practice Perspective - Thompson, M (2007)
Dynamic capability theory argues that organizations' internal capabilities enable sustained competitive advantage. Innovations in work practices (commonly termed ‘high performance’, ‘high commitment’ or ‘high involvement’ practices) are an important source of these internal capabilities but research evidence shows low levels of penetration. Using a practice perspective, case study analysis of 7 establishments in the aerospace sector identifies three themes that are under-attended to in current research on innovations in work practices: industry and production context; distributed nature of management activity, and social embeddedness. Implications for future research are discussed.